A Legal Study on the Protection of Patents under International Intellectual Property Rights - Sabrina, Najwa Maulida (Universitas Ibn Khaldun Bogor, 2025)
The development of science and technology (science and technology) in humans causes everyone to compete to innovate to create new things that can be useful or functional for humans or can produce an item for commercial purposes. Intellectual Property Rights are any goods and rights that are controlled by property rights, this Intellectual Property Rights consist of 7 types, namely brands, copyrights, trade secrets, geographical indications, circuit layout designs including industrial design, and Patents. In each of these types the rules also protect each type of invention. In the field of technology, inventions will be protected by patents. There are problems that often arise related to patents internationally, especially regarding patent protection against uncertainty, international legal protection of patents and the interests of each party in patent problems nationally and internationally, as well as the form of firmness on foreign patents registered in Indonesia by understanding the obligations of the patent owner. Doctrinal law research methods. The author hopes that this article can fulfill the purpose of understanding the provisions regarding Patents not only nationally but also internationally. The results of the study show that Patent Protection is territorial which means that in one agreement it does not necessarily provide protection for other countries as a whole even though there is a convention that guarantees that a person will receive patent protection in each member state, but mechanically this PCT convention simplifies the process of patent protection internationally.